SISTEM PENDIDIKAN SEKOLAH PAMONG PRAJA DI MALANG TAHUN 1956-1972 - Ricka Yuli Setyani; Wisnu Wisnu (KRONIK : Journal of History Education and Historiography, 2017)
The establishment of the School of Civil Service is expected to print cadres who work in the government that allows people. Society no difficulty for all aspects relating to the civil service is bureaucracy for schools create graduates who are ready to work in local government. The long journey of the servant of the state of the education system originally the Dutch colonial era and post-independence education system more adopters of the Dutch education system that is more emphasis on physical exercise. But over time the civil service school in giving more priority to the education of qualified leadership and managerial abilities administrative.Formulation of the problem: 1) How does the education system of the Civil Service School in Malang in 1956 to 1972, 2) How is the contribution of the distribution of the Civil Service School alumni in Malang. The purpose of this study was to knowing school education system of the civil service and contributions of alumni APDN Malang. This study uses historical research that includes heuristics, criticism, interpretation and historiography.The assessment results of this study, successfully obtained the following conclusions. First: The results of this study describing the changes in the education system from the beginning in the Dutch colonial era and the post-independence more adopters of the Dutch education system that is more emphasis on physical exercise. The education system in APDN changed with more emphasis on the concept of the Trinity-centered learning, which includes Teaching, Care and Training. Second: the contribution of alumni occupying the country APDN applied with some dedication of the civil service in politics and public administration at certain positions as village chief, Head, Municipal Police, Assistant Regional Secretary and Regional Secretary, coupled with FNS (Work Unit Governor) . Key words: Civil Service, The education system